2019
DOI: 10.1177/0885328219858456
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of skin fibroblasts collagen synthesis by polydioxanone mats combined with concentrated growth factor extracts

Abstract: The purpose of this study was to combine polydioxanone and concentrated growth factor extracts to enhance the stimulation of fibroblast collagen synthesis by polydioxanone in facial plastic. In this experiment, polydioxanone was prepared as a nanoscale bioresorbable scaffold by electrospinning. The PDO-CGF mat was prepared by loading the concentrated growth factor extract onto the polydioxanone mat by lyophilization after soaking. The diameter of the mat fibers was observed by scanning electron microscopy, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…[59][60][61] It has been reported that freezedried CGFs in composite materials (loaded on chitosan-alginate composite gel or polydioxanone mat) can promote cell osteogenic induction 62 and the synthesis of collagen by fibroblasts. 63 Based on the above, a fdCGF/MBG composite scaffold was proposed and compared with the fibrin gel formation method in the rabbit mandibular defect model (Fig. 5B) by micro-CT scanning, VG staining, histological staining and sequential fluorescence staining.…”
Section: In Situ Bone Regeneration Of Cgf/mbg Composite Scaffoldmentioning
confidence: 99%
“…[59][60][61] It has been reported that freezedried CGFs in composite materials (loaded on chitosan-alginate composite gel or polydioxanone mat) can promote cell osteogenic induction 62 and the synthesis of collagen by fibroblasts. 63 Based on the above, a fdCGF/MBG composite scaffold was proposed and compared with the fibrin gel formation method in the rabbit mandibular defect model (Fig. 5B) by micro-CT scanning, VG staining, histological staining and sequential fluorescence staining.…”
Section: In Situ Bone Regeneration Of Cgf/mbg Composite Scaffoldmentioning
confidence: 99%
“…Yue et al 20 added 1%, 2%, 5% and 10% CGF to the culture medium of rat dermal fibroblasts, and found that cell proliferation was not proportional to CGF concentration. The results showed that 1% and 2% CGF could promote proliferation of rat dermal fibroblasts more significantly than other concentrations of CGF.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, the cell growth and proliferation were not influenced. Yue et al 20 immersed PDO electrospun mats into medium containing CGF, and got the CGF-coated PDO mat through freeze drying. The results showed that 10% and 30% CGF-PDO mats could significantly stimulate proliferation of rat dermal fibroblasts, and promote the synthesis of Col I and Col III because of TGF-β1 released by CGF through raising the secretion of the enzyme collagenase 27 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Generally, multiple growth factors are collected from CGF extracts. 11 Platelet-growth factors are mostly represented by BMPs, transforming growth factor-b1, epidermal growth factor, PDGF, vascular endothelial growth factor, and basic-fibroblast growth factor. 12 In this systematic review, growth factors within CGF has been shown to stimulate the proliferation, migration and angiogenic or osteogenic differentiation of multiple stem cells in maxillofacial field, including dental pulp cells, 13,14 dental pulp stem cells, 15,16 stem cells of the apical papilla, 17,18 periodontal ligament cells, [19][20][21] periodontal ligament fibroblasts, 22 gingiva-derived mesenchymal stem cells, 23 bone marrow-derived stromal cells, 24,25 osteoblast cells, 26 and periosteum-derived cells.…”
mentioning
confidence: 99%
“…Generally, multiple growth factors are collected from CGF extracts 11 . Platelet-growth factors are mostly represented by BMPs, transforming growth factor-β1, epidermal growth factor, PDGF, vascular endothelial growth factor, and basic-fibroblast growth factor 12 .…”
mentioning
confidence: 99%